Kriopreservasi Semen Domba Garut Menggunakan Tris Kuning Telur yang Disuplementasi Omega-3 Minyak Ikan Salmon (CRYOPRESERVATION GARUT SHEEP SEMEN USING TRIS EGG YOLK SUPPLEMENTED OMEGA-3 FISH OIL SALMON) - Nurcholis, Nurcholis; Arifiantini, Raden Iis; Yamin, Mohamad (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
The availability of superior seeds garut sheep relatively few and the unavailability of seed supply ofsuperior male garut sheep that is continuously high productive is also a problem. . The success ofcryopreservation is influenced by the diluent being used. This study aimed was to compare the Tris EggYolk containing omega-3 (TEYO) and Tris used commercial egg yolk plus omega-3 fish oil salmon (TEYOS)to the success of cryopreservation of garut sheep semen. Five garut ram aged 1,5 – 2,0 years were used inthis study. Semen was collected using an artificial vagina, then it was evaluated and divided into twotubes, each of them was diluted with TEYO and TEYOS (50x106 sel/straw), before they then packed intostraws, equilibrated (5°C), and frozen with liquid nitrogen vapour (-130oC) for10 minutes and storedthem in the container (-196oC) for further evaluation. The results showed that post thawing values of thesperm motility, viability and intact plasma membrane were 53,75±2,46; 60,75±2,17and 72,58±2,12%respectively, diluted with TEYOS were higher (P<0,05) than those diluted with TEYOS with the spermmotility, viability and intact plasma membrane only at 41,50±1,25; 50,50±1,04 and 57,58±1,03%respectively. This result demonstrated that the recovery rate of spermatozoa in TEYOS diluent washigher (P<0,05) than TEYO. Its concluded that fish salmon oil omega-3 supplemented in TEYOS better incryopreservation of garut ram semen compared to the TEYO diluent.
Keywords: omega-3, sperm, cryopreservation, garut sheep